PENGARUH PERBEDAAN UMPAN DAN MATA PANCING TERHADAP HASIL TANGKAPAN IKAN LAYUR (Trichiurus sp) DI PALABUHANRATU, JAWA BARAT - Muktiono, Galih Suryo; Boesono, Herry; Fitri, Aristi Dian Purnama (Journal of Fisheries Resources Utilization Management and Technology, 2013)
The activity of hairtail fish catching is usually used handline. It’s because hairtail fish which caught by fishhook still in good and fresh condition, therefore it has high sale value. The purpose of the research was to analyzed the hairtail fish catching by the used of bait and the different size of fish hook then begin to analyzed the interaction between the used of fish hook barb and kinds of bait hairtail fish catching. The research was used experimental fishing methods which have 2 variabel which are bait and the size of fish hook barb with 4 treatmens (bait of tembang, bait of hairtail,the hook with number 8, the hook with number 10). Each experiment must be done with 10 time repeated. Data analysis is using normality test experiment and ANOVA test with SPSS 17.0. The result of test was showed the differences of tembang bait and hairtail bait influence to the amount of hairtail fish catching. The result of bait hairtail number 8 was 43 pieces, tembang bait number 8 is 24 pieces and tembang bait number 10 was 19 pieces. The ANOVA test was showed that the used of fishhook tools with hairtail bait combination and the size of fishhook number 8 is a better ones.